Pilocytic Astrocytoma in Conus Medullaris in an Adult: A Case Report - Parwan, Deepika; Pandey, Mukesh; Kumar, Ranjan (Annals of Pathology and Laboratory Medicine, 2021)
Pilocytic astrocytoma is a rare glioma, seen predominantly in pediatric population and young adults, within first two decades of life. This is often located in deep midline structures such as brainstem and cerebellum. In adults, this tumor occurs in supratentorial location. It is a rare tumor and is frequently misdiagnosed and mistreated. However, being a low-grade tumor with excellent prognosis, if diagnosed correctly, it can be successfully treated by surgery only. We report a case of 45-year-old male adult patient with conus medullaris tumor who complained of numbness and pain in the limbs and incontinence of urine and bowel. The radiology showed a sharp conus medullaris mass, which was provisionally diagnosed as low-grade glioma and was surgically resected. On intraoperative imprint cytology, it was reported as a low-grade glial tumor. Histopathological examination confirmed the diagnosis of Pilocytic astrocytoma. The patient in under follow up and doing fine.